ANALISIS PENGARUH ONLINE COMMUNITY EXPERIENCE DALAM PEMBENTUKAN SIKAP PELANGGAN TERDAHAP MERK DAN CITRA PERUSAHAAN - Al. Agus Kristiadi; Hartoyo .; Eva Z. Yusuf; Dadang Sukandar (Jurnal Manajemen., 2014)
The growth of mobile broadband services has changed the paradigm of mobile phone consumers from information oriented toward social and communication oriented. The customers connected each other as part of digital community. Along with this changes, mobile telecommunications providers have to develop and manage online community as a stage that is easily accessible to all interested customers to this facility. The challenge faced by the company in managing online community is how to collaborate and engage customers to have online community experience that able to create customer attitude toward brand and firm image. The purpose of this research is to analyze how online community experience will influence on the creation of customers attitude toward the brand and firm image and analyze the successful attributes of online community experience that is held and managed by companies. The study is using sample of broadband online community from the largest mobile telecommunications provider in Indonesia. The analysis tools is Structural Equation Modelling (SEM). From this research, we will know the attributes of successful online community experience and the impact of online community experience to the creation of customer attitudes toward the brand and firm image in broadband mobile telecommunications industry in Indonesia.